Stany nadzwyczajne (stan wojenny, stan wyjątkowy, stan klęski żywiołowej) w konstytucji Rzeczypospolitej Polskiej - Miemiec, Marcin (Wydawnictwo Uniwersytetu Wrocławskiego, 2016)
The Constitution regulates the organisation and functioning of the most important organs of the state, the rules governing the relations between the state and citizens, as well as basic rights, freedoms and duties of citizens. The Constitution allows for restriction of these laws only by legislation, and only when it is necessary in a democratic state for its security or for the protection of public order, environmental protection, health and public morality, for the rights and freedoms of others. It is unacceptable to violate the essence of freedoms and rights. The restrictions are subject to police laws’ regulations. When the police measures are insufficient, applicable are legislations on extraordinary measures: martial law, state of emergency, state of natural disaster. The Constitution defines the following rules for the implementation of these states: uniqueness, legality, proportionality, purpose, protection of the legal system basics, protection of the representative bodies. They are the directives of interpretation of other regulations of the discussed Chapter of the Constitution and the regulations of statutes on emergency situations. A kind of competition for legislation on states of emergency may be provisions of the Act on Crisis Management.
Keywords: extraordinary measures; martial law; state of emergency; state of natural disaster